10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Background Modeling studies suggest that simple dietary "swaps" in which just one food is replaced with another could yield both health and environmental benefits, but it remains unclear whether consumers make such changes when prompted. We tested whether recommending swaps improved the healthfulness and reduced the carbon footprint of simulated online grocery selections. Methods and findings In May-June 2025, we recruited 1,201 US adults ages 18+ for a randomized parallel trial. Participants completed 3 weekly study visits. In the first visit, participants shopped in a naturalistic online grocery store with no intervention. They were then randomized in parallel to 1 of 4 trial arms: (1) climate swaps (n = 301), (2) health swaps (n = 300), (3) climate + health swaps (n = 300), or (4) control (n = 300). In the second and third visits, participants completed the shopping task in their randomly assigned trial arm. Participants were not masked to their trial arm. Using intent-to-treat analyses, we assessed 2 primary endpoints: the healthfulness (operationalized as the average Ofcom Nutrient Profiling Model score across the selected items [range: 1-100]) and carbon footprint (operationalized as the average kg of carbon dioxide equivalents [CO2-eq] per kg associated with producing the selected items) of participants' grocery selections. We examined whether outcomes changed from the first (no-intervention) visit to the second and third (intervention) visits in the swaps arms compared to the control arm. The climate (B = 2.4 on the 1-100 scale, 95% CI [1.1, 3.7]), health (B = 4.7, 95% CI [3.3, 6.0]), and climate + health (B = 4.0, 95% CI [2.7, 5.4]) swaps each improved the healthfulness of participants' selections compared to control (all ps < 0.001). The health and climate + health swaps both increased healthfulness more than the climate swaps (ps ≤ 0.02) but did not differ from one another (p = 0.34). The climate (B = -3.3 kg CO2-eq per kg, 95% CI [-4.6, -2.1]; p < 0.001) and climate + health swaps (B = -2.8, 95% CI [-4.1, -1.6]; p < 0.001), but not the health swaps (B = -0.4, 95% CI [-1.7, 0.8]; p = 0.51), reduced the carbon footprint of participants' selections compared to control. The climate and climate + health swaps led to larger reductions in carbon footprint than the health swaps (ps < 0.001) but did not differ from one another (p = 0.43). Swaps' effects on healthfulness and carbon footprint did not differ by age, health consciousness, or environmental consciousness (ps for interactions ≥0.10). The main limitations were that the sample differed somewhat from the US population and study results may not generalize to brick-and-mortar stores. Conclusions Encouraging swaps to more healthful and lower-carbon foods improved the healthfulness and reduced the carbon footprint of online grocery selections. Clinical trials registration ClinicalTrials.gov (NCT#06648226), first submitted October 16, 2024.